1972
DOI: 10.1007/bf01065691
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic relations between initial response to electric shock and rate of avoidance learning in mice

Abstract: The first experiment was designed to determine what proportion of the between-strain variation in rate of avoidance learning could be attributed to strain differences in sensitivity and response topography to electric shock. Measures of jumping at six shock intensities for four inbred strains were collected in a pretest of shock sensitivity. They were then used to derive a shock intensity for each strain which yielded the same amount of jumping for all strains. Avoidance training was administered to other mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…Analysis of consomic strains demonstrated that insertion of A Chr 1 on a B6 background produced an A phenotype and the F1 analysis revealed this phenotype was of intermediate dominance. The pattern of inheritance is in agreement with those of Wahlsten (1972).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Analysis of consomic strains demonstrated that insertion of A Chr 1 on a B6 background produced an A phenotype and the F1 analysis revealed this phenotype was of intermediate dominance. The pattern of inheritance is in agreement with those of Wahlsten (1972).…”
Section: Discussionsupporting
confidence: 76%
“…Previous research has indicated that initial sensitivity to footshock has a genetic component, that is an intermediate mode of inheritance (Wahlsten 1972) and early studies suggested that sensitivity to footshock may be modulated by a single gene (Whitney 1969(Whitney , 1973. Analysis of consomic strains demonstrated that insertion of A Chr 1 on a B6 background produced an A phenotype and the F1 analysis revealed this phenotype was of intermediate dominance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, additional interactions can be expected between stimulus factors and response factors at the instrumental level, since it is well known that response requirements must be evaluated in connection with species-specific defensive behaviors (Bolles. 1971: Wahlsten, 1972.…”
Section: Discussionmentioning
confidence: 99%
“…It can be shown that the expression for estimating ω 2 given by Hays (1963, p. 382) reduces to for a one-way design with equal numbers of subjects per cell. It should be noted that only two reports Wahlsten, 1971) actually presented values for ω 2 . The remainder were derived by the present author.…”
mentioning
confidence: 99%